Effect of land use, habitat suitability, and hurricanes on the population connectivity of an endemic insular bat - Camilo A. Calderón-Acevedo (Nature Portfolio, 2021)
Abstract Urbanization and natural disasters can disrupt landscape connectivity, effectively isolating populations and increasing the risk of local extirpation particularly in island systems. To understand how fragmentation affects corridors among forested areas, we used circuit theory to model the landscape connectivity of the endemic bat Stenoderma rufum within Puerto Rico. Our models combined species occurrences, land use, habitat suitability, and vegetation cover data that were used either as resistance (land use) or conductance layers (habitat suitability and vegetation cover). Urbanization affected connectivity overall from east to west and underscored protected and rustic areas for the maintenance of forest corridors. Suitable habitat provided a reliable measure of connectivity among potential movement corridors that connected more isolated areas. We found that intense hurricanes that disrupt forest integrity can affect connectivity of suitable habitat. Some of the largest protected areas in the east of Puerto Rico are at an increasing risk of becoming disconnected from more continuous forest patches. Given the increasing rate of urbanization, this pattern could also apply to other vertebrates. Our findings show the importance of maintaining forest integrity, emphasizing the considerable conservation value of rustic areas for the preservation of local biodiversity.